2016
DOI: 10.12968/ajmw.2016.10.4.188
|View full text |Cite
|
Sign up to set email alerts
|

Factors increasing vulnerability to sexual violence of adolescent girls in Limuru sub-county, Kenya

Abstract: Aims: The objective of this study was to determine the factors that increase vulnerability to sexual violence of adolescent girls in secondary schools in Limuru sub-county, Kiambu, Kenya. Methods: The study was cross-sectional in nature and collected qualitative and quantitative data on 301 adolescent girls aged 15–19 years. Data collection was achieved through the use of self-administered questionnaires and three focus group discussions. Findings The response rate was 99.67% (300 of 301 questionnaires). Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Alcohol consumption - In various studies, alcohol consumption by women or their partner was found to be positively associated with GBV. Women who drank alcohol on a daily basis were more likely to experience GBV in comparison to women who did not drink alcohol [ 15 , 27 , 36 , 37 , 40 , 46 , 53 ]. Similarly, the likelihood of reporting GBV amongst women was very high when their partners consumed alcohol on a daily basis in comparison to women whose partners did not consume alcohol [ 16 , 21 , 40 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Alcohol consumption - In various studies, alcohol consumption by women or their partner was found to be positively associated with GBV. Women who drank alcohol on a daily basis were more likely to experience GBV in comparison to women who did not drink alcohol [ 15 , 27 , 36 , 37 , 40 , 46 , 53 ]. Similarly, the likelihood of reporting GBV amongst women was very high when their partners consumed alcohol on a daily basis in comparison to women whose partners did not consume alcohol [ 16 , 21 , 40 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%